Television viewing and personality needs of South African adolescents - Daan van Vuuren; J .J. de Beer; S.H.C. du Toit (Communicare)
ACCORDING to the needs-and gratifications approach, a person actively chooses programmes, articles and films and uses the content of this mass media material to gratify certain needs in him or herself. In this paper, results of a longitudinal study of the relationship between certain personality needs on the one hand and the television viewing behaviour and television programme preferences of adolescents on the other hand, are discussed. Based on a large scale South African study of the influence of television on school-going children, the data of approximately 2 000 adolescents, retested from their 12th to 18th year, are used. Multivariate statistical techniques, e.g. profile analysis, were used to analyze the data obtained by various psychometric instruments and questionnaires.